Pembuatan Game Puzzle "Escape : The Answers" Untuk Melatih Problem Solving Anak Berbasis Android - Dikka Wangsa Suryana; Sri Dianing Asri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
Games are one of applications that many people like, including children. The development of games in Indonesia has started rapidly, game is very popular because it has an attractive appearance and cool stories. Games are not only used for playing but can be used for learning. Games can be used by parents or teachers to make children interested in learning by using games as their media, for example making puzzle games as the media. Games can be used by parents or teachers as media for learning to make children interested in learning, for example by making puzzle games as the media. Therefore, the author wants to build a puzzle game which can help in training the problem solving and children's memory. In making this game the author uses the MDLC method (Multimedia Development Life Cycle) and Unity 3D Software.